2018
DOI: 10.1111/iej.13050
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm model systems for root canal disinfection: a literature review

Abstract: The aim of this review was to present an overview of laboratory root canal biofilm model systems described in the endodontic literature and to critically appraise the various factors that constitute these models. The electronic databases MEDLINE, Web of Science and EMBASE were searched up to and including December 2016 to identify laboratory studies using endodontic biofilm models. The following search terms were used in various combinations: biofilm, root canal, in vitro, endodontic, bacteria, root canal infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
158
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(180 citation statements)
references
References 148 publications
(168 reference statements)
3
158
0
8
Order By: Relevance
“…, Swimberghe et al . ). The ATCC 29212 strain used in this study has been reported to be similar to a clinical isolate in CFU counts, biofilm development and architecture (Seneviratne et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…, Swimberghe et al . ). The ATCC 29212 strain used in this study has been reported to be similar to a clinical isolate in CFU counts, biofilm development and architecture (Seneviratne et al .…”
Section: Discussionmentioning
confidence: 97%
“…Since Enterococcus faecalis is a commonly detected and a predominant organism in microbial reinfection, the species was chosen to explore the basic biology of these communities (Love 2001, George et al 2005, Portenier et al 2005, Swimberghe et al 2019. The ATCC 29212 strain used in this study has been reported to be similar to a clinical isolate in CFU counts, biofilm development and architecture (Seneviratne et al 2013), justifying its choice as the model bacterium in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, biofilms at different growth stages have significant differences in biofilm thickness, bacteria count, and bacteria metabolic status, and these differences may lead to differences in their resistance to antibacterial agents. In the current research, the culture time used for biofilm models varies greatly, ranging from 1 to 70 d . Therefore, before starting oral biofilm‐related research, comprehensive biofilm growth kinetic measurements should be performed on the selected biofilm model in order to identify and understand the maturation phase of the biofilm in each particular model.…”
Section: Factors Influencing the Antibiofilm Properties Of Nanoparticlesmentioning
confidence: 99%
“…In addition to the three main factors affecting the construction of oral biofilm models mentioned above, there are other factors that may affect model construction and evaluation of antibacterial properties. These include the method used to sterilize the biofilm carrier, the frequency the medium is changed, the method for obtaining biofilm sample specimens from the oral cavity, and the initial inoculum concentration.…”
Section: Factors Influencing the Antibiofilm Properties Of Nanoparticlesmentioning
confidence: 99%